Refleksje na temat układu przestrzennego administracji publicznej i jego konsekwencji w zakresie administrowania - Rabska, Teresa (Wydział Prawa i Administracji UAM, 1992)
The science of administrative law has not yet elaborated the concept of region or regionalization. From the perspective of t h a t science, the problem is reduced to t h e territorial division of t h e state, which division determines the spatial range of activities of public administration, governmental as well as local. On the other hand, creating a territorial network, subordinated to the needs of administration and being of formal character, is always a form of interference in a given environment. Such an action brings about further effects, both legal and factual. In consequence, it may either create better conditions for development, or destroy the existing structures. The changes in the administrative structure of t h e state have been implemented only at the oasic level, i.e., at the level of a commune. However, the introduction of local government has not changed the existing structures. Presently, changes should be introduced at the level of governmental administration. The starting point for such changes should be the determination of a new character and a new division of tasks.
Reflecyions on spatial arrangement of administration and its consequences for administrative activities